PENGARUH BUDAYA ORGANISASI DAN PERAN AUDITOR INTERNAL TERHADAP PENCEGAHAN KECURANGAN DENGAN KOMPONEN STRUKTUR PENGENDALIAN INTERNAL SEBAGAI VARIABEL INTERVENING (Studi Empiris Pada Inspektorat Provinsi, Kabupaten dan Kota Jayapura) - Christi Novita Lorensa; Syaikhul Falah; Mariolin Sanggenafa (Fakultas Ekonomi dan Bisnis, Universitas Cenderawasih, 2018)
This study aims to look at factors that influence fraud prevention consisting of organizational culture, the role of internal audit, and internal control components. The controlling component here servesas an intervening variable. The population of this study are internal government auditors working in Inspectorate of Papua Province, Inspectorate of Jayapura City and Inspectorate of Jayapura Regency. The hypothesis in this study was tested using spss 16. The results showed that organizational culture, the role of Internal Auditor and internal control system have a significant positive effect onfraud prevention in Inspectorate of Papua Province, Jayapura City and Jayapura Regency. Organizational culture does not affect the prevention of fraud through the implementation of internal control components and the role of internal auditors does not affect the prevention of fraud through the implementation of internal control systems